Processing Self-Related Information Under Non-attentional Conditions Revealed by Visual MMN - Cheng, Sizhe; Li, Xinhong; Zhan, Qingchen; Wang, Yapei; Guo, Yaning; Huang, Wei; Cao, Yang; Feng, Tingwei; Wang, Hui; Wu, Shengjun; An, Fei; Wang, Xiuchao; et al. (Frontiers in Human Neuroscience, 2022)
Mismatch negativity (MMN) of event-related potentials (ERPs) is a biomarker reflecting the pre-attentional change detection under non-attentional condition. The current study was performed to explore whether high self-related information could elicit MMN in the visual channel, indicating the automatic processing of self-related information at the pre-attentional stage. Thirty five participants were recruited and asked to list 25 city names including the birthplace. According to the difference of relevance reported from the participants, we divided different cities’ name into high (birthplace as deviants), medium (Xi’an, where participants’ university is located, as deviants), and low (totally unrelated cities as standard stimuli) self-related information. VMMN was elicited by high self-related information but not by medium self-related information, with an occipital-temporal scalp distribution, indicating that, under non-attentional condition, compared with low self-related information, high self-related information can be effectively processed automatically in the pre-attentional stage. These data provided new electrophysiological evidence for self-related information processing.